Rooted in the Mangrove Landscape: Children and their Ethnoichthyological Knowledge as Sentinels for Biodiversity Loss in Northern Guinea-Bissau - Keleman, Pieter-Jan; Padrão Temudo, Marina; Moutinho Sá, Rui (Ethnobiology Letters, 2023)
Biomonitoring fish species losses in data-deficient estuaries of West Africa can be facilitated by consulting small-scale fishermen as on-the-spot sentinels. Children are often prominent fishing actors in rural societies, but scientific studies looking at their ethnoichthyological knowledge are lacking. This study examines childhood fish knowledge inside a Diola village in Northern Guinea-Bissau, discussing how gendered division of labor affects the distribution of such knowledge. By using a photo-based identification methodology supplemented with participant observation and key informant interviews, we compare differences in children’s knowledge, perceptions of their mangrove environment, and associated fish diversity. The results show: a) a high level of ethnoichthyological knowledge among the children; b) girls identified fewer fish species than boys; c) both boys and girls show difficulties in correctly naming the fish less visible in the local mangrove ecosystem. We highlight the importance of children’s participation in landscape use and maintenance for their cognitive development. Additionally, we conclude that the assessment of children’s endogenous knowledge is important for biological conservation, securing fish diversity, and sustainable exploitation efforts in mangrove socio-ecosystems while respecting local bio-cultural identity.